Community-Based Rehabilitation for Persons with Severe Mental Illness in a Rural Community of Karnataka: Methodology of a Randomized Controlled Study. Issue 6 (December 2020) - Sivakumar, Thanapal; Thirthalli, Jagadisha; Kumar, C. Naveen; Basavarajappa, Chethan
Background: Task shifting has been recommended as a strategy to reach out to persons with mental illness and bridge the treatment gap. There is a need to explore task-shifting using existing health staff like Accredited Social Health Activists (ASHAs). Aim and Context: ASHAs are involved in ongoing community-based rehabilitation (CBR) program run with a public–private partnership over the last 5 years at Jagaluru Taluk (an administrative block) in Davanagere district (Karnataka, India). This article aims to summarize a randomized controlled trial (RCT) to examine whether CBR delivered by ASHAs is more effective than treatment as usual (TAU) control group in reducing disability associated with severe mental illness (SMI). Method: A group of proactive ASHAs is already working with us for a follow-up of persons with SMI. For the study, we would allocate areas that are currently not being covered proactively by ASHAs randomly in a 1:1 ratio via computer-generated randomization list to receive either ASHAs delivered CBR arm or TAU control group. A sample size of about 100 in each arm is enough to identify an effect size of 0.5 in total IDEAS score between the intervention and control arms with a power of 90% and an alpha of 0.05. We use the SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) statement to describe the methods of the trial. Result: The study has been approved by the institute ethics committee and registered with CTRI (CTRI/2019/08/020585 dated 6th August 2019). The recruitment of subjects is ongoing. The patients will be followed up for 1 year and assessed. The trial is funded by the Indian Council of Medical Research, Government of India. Discussion: The results of the study will be helpful from a public health perspective in delivering cost-effective and replicable CBR for persons with SMI through ASHAs. If the model turns successful, this could be expanded throughout the state/country. This would go a long way in bridging the huge treatment gap.